2022
DOI: 10.1038/s41467-022-33840-6
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intake of high dietary sucrose induces sexually dimorphic metabolic adaptations in mouse liver and adipose tissue

Abstract: Almost all effective treatments for non-alcoholic fatty liver disease (NAFLD) involve reduction of adiposity, which suggests the metabolic axis between liver and adipose tissue is essential to NAFLD development. Since excessive dietary sugar intake may be an initiating factor for NAFLD, we have characterized the metabolic effects of liquid sucrose intake at concentrations relevant to typical human consumption in mice. We report that sucrose intake induces sexually dimorphic effects in liver, adipose tissue, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 89 publications
3
2
0
Order By: Relevance
“…Principal component analysis (PCA) revealed that liquid sucrose ingestion resulted in the largest transcriptional changes in the liver and vWAT ( Fig. 3a ), which is consistent with previous results (Stephenson et al, 2022). Of note, we observed that JNK-IN-5A treatment, especially JNK_D1, corrected to a large extent of the gene expression profile in the liver and vWAT of treated-rats towards the profile of healthy controls on a principal components space ( Fig.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Principal component analysis (PCA) revealed that liquid sucrose ingestion resulted in the largest transcriptional changes in the liver and vWAT ( Fig. 3a ), which is consistent with previous results (Stephenson et al, 2022). Of note, we observed that JNK-IN-5A treatment, especially JNK_D1, corrected to a large extent of the gene expression profile in the liver and vWAT of treated-rats towards the profile of healthy controls on a principal components space ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…Principal component analysis (PCA) revealed that liquid sucrose ingestion resulted in the largest transcriptional changes in the liver and vWAT (Fig. 3a), which is consistent with previous results (Stephenson et al, 2022).…”
Section: Jnk Inhibition Rewires Metabolic Perturbation In the Liver A...supporting
confidence: 90%
See 2 more Smart Citations
“…As others have observed ( 56 ), there were sex differences in the response to diet and colon cancer. Typically, male mice gain weight earlier compared with female mice while on a HFD.…”
Section: Discussionsupporting
confidence: 73%